2020
DOI: 10.1038/s41379-020-0599-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of 34 Japanese patients with EBV-positive mucocutaneous ulcer

Abstract: Epstein-Barr virus (EBV)-positive mucocutaneous ulcer (EBVMCU) is a unifocal mucosal or cutaneous ulcer that is histologically characterized by proliferating EBV-positive atypical B cells. While EBVMCU demonstrates a histology similar to that of EBV-positive diffuse large B-cell lymphoma (DLBCL), their clinical behavior differs.Thus, characterizing distinguishing features of EBVMCU and EBV-positive DLBCL is critical. To identify unique characteristics between EBVMCU and lymphoma, we analyzed the clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 28 publications
4
87
2
Order By: Relevance
“…Several previous studies of EBVMCU in the context of MTX-LPD reported good clinical outcomes associated with this diagnosis. 17,[19][20][21] Of note, the incidence of EBVMCU in association with MTX-LPD is higher than that of age-related EBVMCU. 17 The mechanism underlying the markedly high rate of spontaneous regression in response to drug discontinuation among patients in this specific MTX-LPD cohort remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies of EBVMCU in the context of MTX-LPD reported good clinical outcomes associated with this diagnosis. 17,[19][20][21] Of note, the incidence of EBVMCU in association with MTX-LPD is higher than that of age-related EBVMCU. 17 The mechanism underlying the markedly high rate of spontaneous regression in response to drug discontinuation among patients in this specific MTX-LPD cohort remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21] Of note, the incidence of EBVMCU in association with MTX-LPD is higher than that of age-related EBVMCU. 17 The mechanism underlying the markedly high rate of spontaneous regression in response to drug discontinuation among patients in this specific MTX-LPD cohort remains unclear. Among the possibilities, EBV-positive MTX-LPD may be associated with significant impairment of cytotoxic T-cell function due to the combined effects of RA and MTX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous cases where CHL is identified within the GI tract, it has been linked to clinical histories such as non-Hodgkin lymphoma, inflammatory bowel disease, and immunosuppression [ 3 , 4 ]. A newly described entity, Epstein-Barr virus-positive mucocutaneous ulcer (EBVMCU), shows features which overlap with CHL [ 5 , 6 ]. Differentiation of these two diagnoses is critical for guiding appropriate treatment decisions as EBVMCU may respond to reduction in immunosuppressant while CHL may need chemotherapy.…”
Section: Introductionmentioning
confidence: 99%